Studies of x-ray emission properties of photoionized plasmas. (8th March 2016) - Wang, Feilu; Han, Bo; Jin, Rui; Salzmann, David; Liang, Guiyun; Wei, Huigang; Zhong, Jiayong; Zhao, Gang; Li, Jia-ming
Abstract: In this paper three aspects of photoionized plasmas are discussed in both laboratory and astrophysical contexts. First, the importance of accurate atomic/ionic data for the analysis of photoionized plasmas is shown. Second, an overview of present computer codes for the analysis of photoionized plasmas is given. We introduce our computer model, radiative-collisional code based on the flexible atomic code (RCF), for calculations of the properties of such plasmas. RCF uses database generated by the flexible atomic code. Using RCF it is shown that incorporating the satellite lines from doubly excited Li-like ions into the He triplet lines is necessary for reliable analysis of observational spectra from astrophysical objects. Finally, we introduce a proposal to generate photoionized plasmas by x-ray free electron laser, which may facilitate the simulation in lab of astrophysical plasmas in photoionization equilibrium.